HYPERTHERMIA EFFECT ON HUMAN NORMAL BREAST (MCF-10A) AND CANCER (MDA-MB 231 AND MCF-7) CELLS - ELENGOE, ASITA; MOHAMMED ALITHEEN, NOOR JAHAN BANU; HAMDAN, SALEHHUDDIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In this study, the hyperthermia effect on the viability of human normal breast (MCF-10A) and cancer (MDA-MB 231 and MCF-7) cells was evaluated by MTT assay. Methods: Cells were exposed to heat at 38ºC, 39ºC, 40ºC, 41ºC, 42ºC, 43ºC, and 44ºC for five different durations of heat exposure (0.5, 1, 2, 3, and 4 h). Breakpoint temperatures of MCF-10A, MDA-MB 231, and MCF-7 were determined using cumulative equivalent 43°C (CEM43) model. This model was first time used to calculate thermal isoeffect dose (TID) for MCF-10A, MDA-MB 231, and MCF-7. Results: MCF-10A started to die at 42°C for 3 h while MDA-MB 231 and MCF-7 need a temperature of 38°C for 0.5 h; thus, they were identified as the threshold temperatures in CEM43 model. Furthermore, the effect of “43°C incubator 2 h” had similar total thermal dose as “44°C incubator 0.5 h” for MDA-MB 231 and MCF-7. In addition, “43°C incubator 3 h” effect had also almost the same thermal dose as “44°C incubator 1 h” for MDA-MB 231 and MCF-7. Conclusion: A better understanding of the significant correlations between CEM43 and response parameters in clinical trials could be useful to treat breast cancer patients.